Ciprofloxacin susceptibility of Pseudomonas aeruginosa isolates from keratitis - Lomholt, J A (© 2003 British Journal of Ophthalmology, 2003)
Aim: To examine the ciprofloxacin susceptibility of 106 Pseudomonas aeruginosa eye isolates from the United Kingdom, Denmark, India, the United States, and Australia, and to determine the molecular mechanisms of resistance. Methods: Ciprofloxacin susceptibility was tested by an agar dilution method; genomic DNA corresponding to the quinolone target genes gyrA and parC, and the regulatory genes mexR and nfxB controlling drug efflux systems, was amplified by PCR and sequenced; multilocus enzyme electrophoresis was performed to examine the genetic relation among resistant strains. Results: Three out of 90 keratitis isolates (3.3%), one from the United Kingdom and two from India, exhibited MIC values of 16 mg/l or 32 mg/l. The UK isolate had a mutation in gyrA (Thr83Ile), whereas the two Indian isolates showed mutations in both gyrA (Thr83Ile) and parC (Ser87Leu). The remaining isolates from keratitis, endophthalmitis, contact lens associated red eye (CLARE), and contact lens storage cases showed MIC values below 1 mg/l. Several allelic forms of gyrA and a single variation in the mexR gene product were detected in 10 ciprofloxacin susceptible strains. Conclusions: The vast majority of eye isolates of P aeruginosa from European countries are fully susceptible to ciprofloxacin and the concentration of ciprofloxacin eye drops used for local treatment (3000 mg/l) exceeds MIC values for strains recorded as resistant. Mutations in more than one target gene were associated with higher MIC values.